DAMPAK SEBELUM DAN SESUDAH TERJADINYA COVID-19 TERHADAP ABNORMAL RETURN DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM KELOMPOK PERUSAHAAN LQ45 DI BEI - Intan Zoraya; Vika Fitranita; Indah Oktari Wijayanti (Management Insight: Jurnal Ilmiah Manajemen, 2021)
This study examines the impact before and after the occurrence of covid-19 on abnormal returns and stock trading volume activities on the IDX. The population in this study were all companies listed on the Indonesia Stock Exchange during January 2020 to June 2020. Based on the results of the data processing, the first hypothesis was accepted, namely that there were differences in the average abnormal returns obtained by investors before and after the Covid-19 incident at LQ 45. The second hypothesis in the data processing of this research is that there is a difference in the average stock trading volume activity before and after the Covid-19 event. Based on the results of the study, this shows that investors experience panic and fears of loss caused by Covid-19 and spur investors to sell their shares.